3D printed polymers are less stable than injection moulded counterparts when exposed to terminal sterilization processes using novel vaporized hydrogen peroxide and electron beam processes. (21st November 2019) - Chen, Yuanyuan; Neff, Martin; McEvoy, Brian; Cao, Zhi; Pezzoli, Romina; Murphy, Alan; Gately, Noel; Jnr, Michael Hopkins; Rowan, Neil J.; Devine, Declan M.
Abstract: There is an increasing trend for use of 3D printing processes in healthcare due in part to emergence of customised medical devices and associated low manufacturing cost. However, there is a dearth of knowledge on the efficacy of terminal sterilization processes on such 3D printing processes compared to conventional manufacturing methods, such as injection moulding. Therefore, the goal of this timely work was to compare the mechanical, thermal and chemical effects of vaporized hydrogen peroxide (VHP) and electron beam (E-beam) sterilization processes on the 3D printed and injection moulded high density polyethylene (HDPE) and Polyamide 6 samples. Characterization of materials post sterilization was performed by several analytical methods. Studies found that injection moulded samples exhibited higher tensile strength, higher degree of crystallinity, lower ductility, and higher thermal stability than 3D printed samples due to their tightly packed structures. After VHP and E-beam sterilization processes, oxidation and crosslinking occurred along with yellow colour change. Free hydroxyl radicals and intermolecular carbon bonding were detected by FTIR; the viscosity, storage modulus and loss modulus were increased due to crosslinking; the wettability of all the samples were increased due to the free radicals on the surface. However, the tensile properties of all samples measured were not affected by the VHP or E-beam processes, which was attributed to the low irradiation dosage of E-beam and good resistance to hydrolytic degradation from VHP. Overall, E-beam process resulted in more severe oxidation and crosslinking than VHP process, and sterilized 3D printed samples were less stable compared to injection moulded samples when exposed to terminal sterilization processes, which was evidenced with more new peaks related to oxidation and crosslinking detected by FTIR and the dramatic increase in the degree of crystallinity. These findings highlight the importance of considering choice of industrial terminal sterilization with view to future reduction of processing conditions for emerging additive manufacturing processes, such as in situ 3D printing that is often underappreciated. Graphical abstract: Image 1 Highlights: Injection moulded objects are stronger but less ductile than 3D printed objects. Injection moulded objects are more stable than 3D printed objects upon sterilization processes. E-beam caused more severe oxidation and crosslinking than VHP.